iMSC‐Derived Extracellular Vesicles Improve Atopic Dermatitis by Augmenting Skin Barrier Integrity and Inhibiting Inflammation, Pruritus and Th2 Immune Responses - Soo Kim; Jimin Kim; Ran Kim; Hongduk Kim; Seul Ki Lee; Seon‐Yeong Jeong; Haedeun You; Somi Park; Tae Min Kim (Journal of Extracellular Biology)
ABSTRACT Atopic dermatitis (AD) is a chronic inflammatory disease characterized by severe itching and eczematous lesions. Despite various treatments, AD patients experience side effects and fail to achieve full remission. This study investigated the therapeutic potential of extracellular vesicles (EVs) derived from IFN‐γ‐primed induced mesenchymal stem cells (IFN‐γ‐iMSC‐EVs) in a 2,4‐dinitrochlorobenzene (DNCB)‐induced AD mouse model. We also examined whether IFN‐γ‐iMSC‐EVs could suppress IL‐4/13‐induced Th2 responses in keratinocytes. The therapeutic outcome of IFN‐γ‐iMSC‐EVs was comparable to or more effective than baricitinib or clobetasol. While severe weight loss was observed in mice treated with clobetasol, no significant weight reduction occurred in those receiving IFN‐γ‐iMSC‐EVs. Histological analysis demonstrated reduced skin thickness, decreased infiltration of mast cells and inflammatory cells, and suppression of the Th2 immune response, as evidenced by decreased signalling of IL‐4, IL‐13, and IL‐31. IFN‐γ‐iMSC‐EVs also led to a greater reduction in inflammation and pruritus compared to baricitinib and clobetasol. Additionally, skin barrier integrity and epidermal protein expression were improved in IFN‐γ‐iMSC‐EVs. In IL‐4/13‐stimulated keratinocytes, the decrease in JAK1/2 gene expression and the increase in Keratin 1 gene expression were more prominent in IFN‐γ‐iMSC‐EVs than in baricitinib. The results suggest that IFN‐γ‐iMSC‐EVs have the potential to inhibit AD progression and represent a novel therapeutic option for AD.